Comparison of Alvarado score, appendicitis inflammatory response score (AIR) and Raja Isteri Pengiran Anak Saleha appendicitis (RIPASA) score in predicting acute appendicitis. Issue 1 (January 2023) - Zeb, Muhammad; Khattak, Sabir Khan; Samad, Maryam; Shah, Syed Shayan; Shah, Syed Qasim Ali; Haseeb, Abdul
Abstract: Introduction: Acute Appendicitis is the most common surgical emergency encountered in emergency departments. To prevent the rate of negative appendectomies, different systems i.e. Alvarado score and Appendicitis Inflammatory Response Score (AIR) scores were used, but their diagnostic accuracy in Asian population is questionable. Raja Isteri Pengiran Anak Saleha (RIPASA) score has showed promising results in the recent literature. The purpose of this study is to compare the efficacy of Alvarado, AIR and RIPASA scores in the diagnosis of acute appendicitis. Methods: Alvarado, AIR and RIPASA scores were prospectively applied to 132 included patients that were admitted with provisional diagnosis of acute appendicitis and then their surgery was performed in General Surgery Unit, Hayatabad Medical Complex Peshawar, Pakistan from 1st January 2022 to 31st July 2022. Final diagnosis was confirmed by histopathology report and scores were correlated with final report. Cut off value of score >7, >5 and >7.5 were set for Alvarado, AIR and RIPASA score, respectively according to previous literature. Statistics analysis was done for all 3 scoring systems on SPSS version 23. Results: Of 132 patients, there were n = 79(59.8%) males and n = 53(40.2%) females. Mean age was 24 years (SD ± 11.6) with youngest patient of 9 years and oldest one was 70 years old. Negative Appendectomy rate was 8.3%(n = 11). RIPASA score was superior to AIR and Alvarado score in Sensitivity, NLR, Accuracy and Area under the Curve. AIR score performed better in specificity, NPV, PLR compared to RIPASA and Alvarado score. Conclusion: RIPASA score is an overall better scoring system in diagnosing acute appendicitis in compared to Alvarado and AIR score.